Performance of accountants information processing tasks using REA and BNF representation: A cognitive FIT perspective - Tahir, Agoos Munalis; Ismail, Shahifol Arbi; Danila, Raudah (Universiti Utara Malaysia, 2004)
In this study we examine and explain the performance of accountants' information processing tasks in cognitive fit perspective. Performance is defined as time taken to complete a task (efficiency) and the percentage of score for each task (accuracy). Cognitive fit theory postulates that tasks and representations which cognitively fit will result in better performance. In this experimental study, thirty nine students were selected as subjects completing three types of task (i.e search, recognition and inference) using two different representations (i,e REA and BNF). The result shows that for tasks which use high cognitive engagement (i.e recognition and inference tasks), cognitive fit effects the accountants' information processing performance. While for the task which uses low cognitive engagement (i.e. search), cognitive fit does not effect the performance.